FINANCIAL INTERMEDIATION AND SMALL AND MEDIUM ENTERPRISES PERFORMANCE IN NIGERIA (AN AGGREGATED ANALYSIS: 1980-2013) - Anigbogu, Theresa Ukamaka; Okoli, Ikechukwu Moses; Nwakoby, Nkiru Peace (European Scientific Journal, ESJ, 2015)
Small and Medium Enterprises (SMEs) plays a unique role in every economy and Nigeria inclusive. That notwithstanding, the performance of Small and Medium Enterprises (SMEs) in Nigeria is reported in the literature to be very low in terms of survival rate and contribution to Gross Domestic Product (GDP) despite government intervention. Against this backdrop, this study investigates the effect of financial intermediation on small and medium enterprises performance in Nigeria using an econometric model of the Ordinary Least Square (OLS). Findings reveal that with the exception of bank interest rate to SMEs, all other variables - financial intermediation, commercial bank loans and advances to SMEs, bank lending rate to SMEs, exchange rate and monetary policy - have a positive and significant influence on small and medium enterprises performance in Nigeria. The study recommends that the Nigerian government should design an accessible and a well supervised SMEs credit scheme for the development of the sector. An appropriate environment and infrastructural facilities for SMEs development should be provided by the government so as to facilitate commercial bank loans and advances with good Bank lending and interest rate to SMEs. The government should also influence the foreign exchange rate, by positive economic reforms through its monetary policies that will reduce the adverse effect of unstable foreign exchange rate on the Nigerian economy with respect to trade flow. This will induce growth in the sector.